A synoptic review of the Amphibians of Iran: bibliography, taxonomy, synonymy, distribution, conservation status, and identification key to the eggs, larvae, and adults - Safaei-Mahroo, Barbod; Ghaffari, Hanyeh; Niamir, Aidin (Zootaxa, 2023)
This study provides an illustrated account, a comprehensive update of the systematics, and a bibliography of the 15 species of anurans in five families, eight genera; and of the six species of urodeles in two families, four genera in Iran. Bufonidae, with eight species, is the most diverse family; Salamandridae has five species and Ranidae has four species. This study also presents updated identification keys for the eggs, larvae, and metamorphosed amphibians of Iran. We designated specimen NMW 19855.1 as neotype of Pelophylax persicus (Schneider, 1799) comb. nov.. Along with distribution maps obtained from all the reliable localities and museum specimens known at this time, the modelled habitat of species, and for the first time, the National Red List of amphibians based on the IUCN red list categories and criteria. Based on our evaluation we propose to categorize Bufo eichwaldi, Paradactylodon persicus, Neurergus derjugini, and N. kaiseri as Vulnerable at National Red List, and to move Bufotes (Calliopersa) luristanicus, B. (C.) surdus, Firouzophrynus olivaceus, and Rana pseudodalmatina from the category of Least Concern (LC) to Near Threatened (NT). The National Red List of amphibians that we propose has significant implications for endangered species management and conservation. Forty-one percent of amphibian species in Iran are endemic to the country, and more than forty percent of the Iranian amphibians are at risk of extinction. Zagros Mountain forest and Hyrcaniain forests have more than 80% (i.e. 18 species) of the diversity of Iranian amphibians. A considerable amount of scientific literature published on Iranian amphibians in Persian language is not easily accessible to researchers outside Iran. This monograph attempts to remedy the situation and provides broader access to international herpetology. We recognize that taxonomy is always in a state of flux, and the names and synonymies used here reflect our current view.